PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 23 PINGGIR KABUPATEN BENGKALIS - Farlena, Hasni; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was science studies students achievement in fifth graderes (VB) SDN 23 Pinggir is still low with an average value 68,50 (with KKM 70). The purpose of this research was to improve the students achievement of the fifth graderes (VB) SDN 23 Pinggir with implementation of cooperative learning model type Numbered Heads Together. This research was an classroom action research with two cycles in second semester 2014/2015. Before implementation of cooperative learning model type Numbered Heads Together average 68,50, after implementation of cooperative learning model type Numbered Heads Together, UH I was 73,25 that improve 7% from before exam with average 68,50. UH II was 79,50 that improve 16%. Teacher’s activities with the implementation of cooperative learning model type Numbered Heads Together at first meeting of first cycle was 54,1% (enough category), and second meeting was 66,6% (enough category) that improve 12,5 point. At second cycle, teacher’s activities at first meeting was 79,2% (good category) that improve 12,6 point from second meeting of first cycle. Second meeting of second cycle was 91,7% (verygood category) which improve 12,5 point. Students activities at first meeting of first cycle was 50% (enough category), and second meeting 62,5% (enough category) that improve 12,5 point. At second cycle, student’s activities at first meeting was 75% (good category) that improve 12,5 point from second meeting of first cycle. Second meeting of second cycle was 87,5% (verygood category) which improve 12,5 point. Implementation of cooperative learning model type Numbered Heads Together can improved science studies students achievement of fifth graders (VB) SDN 23 Pinggir.Key Words : Cooperative Learning Model Type Numbered Heads Together (NHT), Fifth graderes students Achievement.